People, nations and traditions in a comparative frame thinking about the past with Jonathan Steinberg - Coffman, D'Maris 1973-; James, Harold 1956-; Di Liberto, Nicholas ca. 20./21. Jh (Anthem Press, 2021)
The diverse essays in this book reflect Jonathan Steinberg's methodological pluralism and insatiable curiosity for historical questions which cross disciplinary and geographical boundaries. Animating students, colleagues, friends and wider audiences with his enthusiasm for 'thinking about the past' was his vocation, one that he pursued with unmatched enthusiasm. Through this collection of essays, the book hopes to convey something of the intellectual range, analytical purchase and moral purpose of his historical writing and teaching. One feature of Steinberg's inspiring and charismatic lectures was his unique ability to combine an analysis - always fresh, never pre-cooked - of big historical structures and trends with an acute awareness of the importance of individual personalities. Jonathan Steinberg also believed in contingency, the importance of chance, and was keen to reject any form of historical determinism. The third salient feature of his work was his sense of moral purpose. He understood history as a hermeneutic science and was appropriately cautious about the epistemological status of historical claims, but he nevertheless saw the correctness of historical arguments and the probity of historical claims to be moral as well as empirical questions. His ethical sensibilities, his openness to interdisciplinary work and the humane and nuanced understanding of human motivation equipped him to tackle some of the most difficult subjects of nineteenth- and twentieth-century European history